Assessment of the Influence of Hydrogen Share on Performance, Combustion, and Emissions in a Four-Stroke Gasoline Engine - Md. Nurun Nabi (13887553) (2022)
This study aims to develop a one-dimensional model to investigate the effect of hydrogen share in gasoline fuel on the performance, combustion, and exhaust emissions of a gasoline direct-injection engine. Iso-octane was used as a reference fuel to compare performance, combustion, and emission parameters. The model was developed using commercial GT-Suite and ANSYS software. The simulation results using GT-Suite were validated with the published data and ANSYS results. The hydrogen fractions were varied from 0% to 11.09% to validate the simulation results with the published results. The investigation continued with three higher hydrogen fractions (15%, 20% and 25%) to study the performance, combustion, emissions, and sustainability parameters. Compared to neat gasoline, hydrogen-shared fuels show a maximum 2% higher exergy efficiency, 51% higher exergy and 42% energy rates while reducing carbon dioxide (CO2) emissions by 51% with a penalty of nitrogen oxide emissions (NOx) by 62% at an excess ratio of 1.3. Other novel findings, including higher sustainability indices, lower depletion potentials, and lower unitary cost indices with higher-fraction hydrogen fuels, suggest that they are environmentally and economically sustainable. In the second part of this study, the NOx formation mechanism and its associated factors, including in-cylinder temperature, heat transfer rate, cumulative heat release, and burned rate, were confirmed and compared with gasoline and neat ethylene. Other Information Published in: IEEE Access License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1109/access.2022.3177751